Penafsiran Ayat-Ayat Komunikasi Orang Tua dan Anak Perspektif Tafsir Sufi Al-Qushayrī - Suliyono M. Mubarok (Refleksi: Jurnal Kajian Agama dan Filsafat, 2019)
This paper discusses the interpretation of verses of al-Qushayrī’s parent and child communication perspective. The purpose of this discussion is to explore the variety of communication with the value of the akhlāqī sufistic message between parents and children who are the object of discussion. The objects of this research are the Prophet Ibrāhīm and Ismā’il, Luqmān al-Ḥakīm and his son, Ya’qūb, Yūsuf and his brothers, Nūḥ and Kan’an. The importance of revealing the side of Sufism, many Sufis interpret the Qur’an far beyond the reading of verses in an ancient way. Laṭāif al-Ishārāt one of them, this interpretation includes moderate sufistic interpretation which is not only based on the inner meaning (esoteric) of the verse, but also holds to the meaning of its birth (exoteric). The influence of Sufism has impli-cations in interpreting the Qur’an. Thus the Sufistic values that can be taken from the parent and child communication verses can be mapped as follows: The value of tawḥid, ṣabar, maḥabbah, murāqabah, raja’, riḍa, and tawakal.